Investigation of biomass productivity from Nannochloropsis gaditana via response surface methodology using MATLAB - Aytun Onay (Energy Reports, 2020)
This study aimed to investigate biomass productivity to produce bioethanol from Nannochloropsis gaditana grown in Johnson's medium including different concentrations of macronutrients. For this study, we prepared various concentrations of KNO3 (0.1-2 g/L), NaHCO3 (5-50 g/L) and KH2PO4 (0.05-0.8 g/L). In addition, central composite design (CCD) was used to optimize biomass productivity for acquiring the maximum biomass productivity. It was found that biomass concentration may vary with macronutrient concentrations. According to the experimental results, the maximum biomass concentration was found in 0.5, 20 and 0.8 g/L of KNO3, NaHCO3 and KH2PO4, respectively. The maximum experimental biomass yield of 2.04 g/L was obtained at these optimum conditions. These results showed that Nannochloropsis gaditana can be used for bio-ethanol production after optimization of macronutrient concentration.
Keywords: 330; Biomass production; Central composite design; Macronutrients; Quadratic model